Integration of Entrepreneurship Education With Biology Education Study Program Courses: Student Perceptions - Husni, Rafeah; Nasution, Yusnita Anwar (Bioedunis Journal, 2024)
This study aims to explore biology education students' perceptions of integrating entrepreneurship education with courses, interest in entrepreneurship, and self-efficacy. This study is an exploratory descriptive research, the respondents were 77 biology education students at UIN SYAHADA Padangsidimpuan. The instrument used was a closed questionnaire with the Guttman scale. Research data was analyzed descriptively and inferential statistics using the Kruskal Wallis test. The results of the study are: 1) student perceptions regarding the integration of entrepreneurship education are very positive, as many as 83.1% of students feel that integration needs to be implemented. Based on the Sig value (0.86 0.05), there is no significant difference between the perceptions of semester III, V, and VII students; 2) Students' entrepreneurial interest is relatively high, namely 77.9% of students are interested in entrepreneurship. Based on the Sig value (0.43 0.05), there is no significant difference between the interests of semester III, V and VII students; 3) Student self-efficacy in entrepreneurship is classified as moderate, namely only 50.6% of students believe in their abilities. Based on the Sig value (0.07 0.05), there is a significant difference between the self-efficacy of students in semesters III, V, and VII.